TROUBLESHOOTING PROFILE SOLVING CLASS STUDENTS VII SMPN 4 PALU IN TERMS OF LEARNING STYLE - Hikmah, Nurul; Nurhayadi, Nurhayadi; Rizal, Muh.; Idris, Mustamin (FKIP Universitas Muhammadiyah Tangerang, 2024)
The purpose of this research is to describe the student's problem-solving profile on the reviewed fragmentary material of the learning style. The data collection techniques used are troubleshooting tests and interviews. The results of this study are: (1) the stage of understanding the visual subject's problem is able to understand the subject well and identify the subject by rotating the important thing on the subject. The auditory subject can capture the meaning of the subject so that it can determine the sufficient condition and the necessary condition of the matter by listening to his friend at the time of reading the subject, as well as the kinesthetic subject understands the issue by turning the pencil so that he can catch the significance of the issue and can tell back the information known and asked. (2) the stage making the plan of the visual subject is able to make a plan with the information already known by describing the steps of completion on another sheet, whereas the auditory subject pronounces the strategy well with a loud voice as well as with the kinesthetic subject can make plans with the already known information but make different completion steps. (3) the stage implementing the visual, auditory and kinesthetic subject plan can complete the completion in accordance with the known information and the planned strategy, even though there are errors in the steps on the kinetical subject but the subject is capable of determining completion according to the plan.